Selectivity of insecticides to Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) predator of Ascia monuste orseis (Godart) (Lepidoptera: Pieridae) - Picanço, Marcelo; J. Ribeiro, Luciano; L. D. Leite, Germano; C. Zanuncio, José (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this research was to evaluate the selectivity of Carbaryl, Deltamethrin, Methyl Parathion, Permethrin and Thrichorfon to the predator Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) testing dosages of these insecticides which caused 90% mortality of 4th and 5th instars Ascia monuste orseis (Godart) (Lepidoptera: Pieridae) caterpillars. The most selective insecticide to P. nigrispinus was Permethrin, followed by Deltamethrin and Methil Parathion. Nymphs of 5th instar of this predador were more tolerant to Thrichorfon than adults and nymphs of 3th instar. Females of P. nigrispinus were more tolerant to Methil Parathion than males.